2011
DOI: 10.1258/ar.2010.100369
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and prognostic factors of spontaneous ruptured hepatocellular carcinoma treated with transarterial embolization

Abstract: TAE/TACE is effective for achieving initial hemostasis, which is critical to survival. Regardless of successful TAE/TACE, the survival rate in patients with Child-Pugh class C remains poor. Portal vein thrombosis and tumor extent are significant image parameters for predicting survival after TAE/TACE for ruptured HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 30 publications
0
44
1
Order By: Relevance
“…In this context, it is important to determine an algorithm or guidelines for treatment of patients with a ruptured HCC in consideration of their background and current state. The prognosis of an affected patient is thought to be defined by hepatic reserve function prior to the rupture, total bleeding volume, and HCC progression including portal vein tumor thrombosis [14]. In the present study, prognoses differed between the recurrent and naïve cases, as the former showed a tendency of more advanced stage HCC and worse hepatic reserve function, which may influence prognosis.…”
Section: Discussionmentioning
confidence: 66%
“…In this context, it is important to determine an algorithm or guidelines for treatment of patients with a ruptured HCC in consideration of their background and current state. The prognosis of an affected patient is thought to be defined by hepatic reserve function prior to the rupture, total bleeding volume, and HCC progression including portal vein tumor thrombosis [14]. In the present study, prognoses differed between the recurrent and naïve cases, as the former showed a tendency of more advanced stage HCC and worse hepatic reserve function, which may influence prognosis.…”
Section: Discussionmentioning
confidence: 66%
“…In cases of unstable states or unresectable tumors (with IDRFs), interventional embolization or laparotomy for hemostasis as damage-control surgery might be considered. Interventional embolization is an effective treatment for tumors originating from organs such as the liver and kidney when spontaneous rupture occurs [17][18][19][20]. However, NB originates from the retroperitoneum and usually has no definitive blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, whether the optimal treatment approach for ruptured HCC after successful TAE is staged hepatic resection or repeated TACE remains under debate. Some groups have argued that TACE should be the first treatment for these patients due to their advanced stage, poor overall prognosis, large tumor volume, impaired liver function, and implantation metastasis (Li et al, 2009;Toshikuni et al, 2011;Shin et al, 2011). However, other studies have reported a survival benefit from staged hepatectomy in these cases (Battula et al, 2009;Miyoshi et al, 2011).…”
Section: Patients With Spontaneously Ruptured Hepatocellular Carcinommentioning
confidence: 99%